A diaphragm slurry composition, composite ceramic diaphragm and secondary battery

By using a separator slurry composition of heat-resistant polymer particles and nanoceramic particles in the lithium-ion battery separator, the problem of easy agglomeration of nanoceramic particles is solved, the mechanical strength and heat resistance of the separator are improved, and the electrolyte infiltration is enhanced Reduces battery quality and weight.

CN118738765BActive Publication Date: 2025-01-17SHENZHEN HAODYNE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411191321.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-17
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

During the thinning process of existing lithium-ion battery separators, nanoceramic particles are prone to agglomeration and precipitation, affecting the uniformity of coating and the electrolyte liquid absorption performance, resulting in low quality of the separator and insufficient heat resistance.

Method used

Using a separator slurry composition including heat-resistant polymer particles, nanoceramic particles and binders, the carboxyl and acid anhydride functional groups are introduced through alkali-soluble resins, the surface energy of nanoceramic particles is reduced, the agglomeration is prevented, and the polymer particles are introduced to form spatial barriers. , enhance dispersion stability.

Benefits of technology

The uniform distribution of nanoceramic particles in the polymer matrix is ​​achieved, the mechanical strength, heat shrinkage resistance and electrolyte wetting properties of the separator are improved, and the battery quality and weight are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005149008800000101
    Figure GDA0005149008800000101
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium battery materials, and in particular to a diaphragm slurry composition, a composite ceramic diaphragm and a secondary battery. The diaphragm slurry composition comprises heat-resistant polymer particles, nano-ceramic particles and a binder. The heat-resistant polymer particles comprise an alkali-soluble resin structural unit, a main monomer structural unit, a functional monomer structural unit and a cross-linking monomer structural unit. The glass transition temperature of the heat-resistant polymer particles is ≥150°C; the alkali-soluble resin comprises at least one of a carboxyl group and an acid anhydride, and the glass transition temperature of the alkali-soluble resin is >100°C. The heat-resistant polymer particles can reduce the proximity and aggregation between nano-ceramic particles by means of a barrier. The obtained composite ceramic diaphragm has high thermal stability, high mechanical strength, good electrolyte wettability, and is lighter and thinner than a ceramic diaphragm prepared from inorganic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a diaphragm slurry composition, a composite ceramic diaphragm and a secondary battery. Background Art

[0002] Lithium-ion batteries are mainly composed of positive electrode, negative electrode, separator, electrolyte and battery shell. When charging, external voltage is applied to the two poles of the battery. + It is deintercalated from the positive electrode material, enters the electrolyte, passes through the diaphragm to the negative electrode, and the path is reversed during discharge. When the battery is overcharged or punctured, thermal runaway will occur, posing a safety hazard of battery combustion and explosion. The diaphragm is a key component to prevent thermal runaway. Its main function is to separate the positive and negative electrodes of the battery, thereby preventing the positive and negative electrodes from contacting and short-circuiting. It is also the Li + The only channel for transmission.

[0003] At present, most of the separators in lithium-ion batteries are powder ceramic coated separators. Ceramic separators not only have the good mechanical properties of polyolefin separators, but also combine the good high temperature resistance of inorganic powders, which significantly improves the dimensional stability of separators under high temperature conditions. The main preparation method of ceramic separators is to evenly distribute ceramic particles and ceramic binders in a solvent by dispersion to form a ceramic slurry, and then form a separator coated with a ceramic coating after coating and drying. The secondary battery prepared by the ceramic separator can maintain the integrity of the separator even if large-scale heat release occurs during the charging and discharging process, causing the organic base film to melt, and can prevent the separator from shrinking significantly and causing a momentary battery short circuit.

[0004] With people's pursuit of high energy density and ultra-thin batteries, the thinning of diaphragms has become a hot research direction. From the initial 20μm three-layer dry process to the 12μm wet process membrane, the wet process membrane has also been gradually reduced from 12μm to 9μm, 7μm, and even the extreme value of 5μm, and the trend is to make it thinner and thinner. The thickness of the diaphragm is getting thinner and thinner, and the corresponding diaphragm coating is also getting thinner and thinner; the main ceramic coating thickness today is 2 to 4μm, of which 3μm thick ceramic coating accounts for the vast majority; the reduction of 1μm ceramic coating can significantly improve battery performance and energy density.

[0005] In the prior art, ceramic diaphragms include four main components: ceramic particles, binders, solvents, and additives. Commonly used ceramic particles include powder materials such as silicon dioxide, titanium dioxide, zirconium dioxide, and aluminum oxide. The particle size is mostly micrometer-level. When preparing ceramic slurry, they are easy to agglomerate with each other and disperse unevenly, affecting the coating uniformity, and further affecting the diaphragm's absorption and retention performance of the electrolyte.

[0006] The diaphragm coating in the nano-ceramic coating is a nano-ceramic coating. The smaller the nano-ceramic particle size, the thinner the nano-ceramic coating is under the same surface density, which is in line with the trend of thinner diaphragms. However, due to the large specific surface tension of nano-level ceramics, when a normal ceramic slurry system is used to configure nano-ceramic slurry, the slurry is prone to agglomeration and precipitation due to the small particle size and high density of the nanoparticles. Summary of the invention

[0007] In view of the shortcomings of the prior art, how to provide a slurry composition that is not easy to agglomerate and precipitate, and the lithium battery separator produced has small weight and good heat resistance, has become a technical problem that needs to be solved urgently. Based on this, the present invention provides a separator slurry composition, a composite ceramic separator and a secondary battery. In the present invention, the specific composition of the slurry composition is designed, and the alkali-soluble resin is further introduced to make the slurry composition have excellent dispersibility, and then mixed with nano-ceramic particles to improve the situation that the nano-ceramic particles are easy to agglomerate. The introduced heat-resistant polymer particles with lower density reduce the weight of the separator and improve the heat shrinkage resistance of the separator.

[0008] To achieve this object, in a first aspect, the present invention adopts the following technical solutions:

[0009] A diaphragm slurry composition, comprising heat-resistant polymer particles, nano-ceramic particles and a binder, wherein the heat-resistant polymer particles comprise an alkali-soluble resin structural unit, a main monomer structural unit, a functional monomer structural unit and a cross-linking monomer structural unit, and the glass transition temperature of the heat-resistant polymer particles is ≥150°C;

[0010] The alkali-soluble resin includes at least one of a carboxyl group and an acid anhydride, and the glass transition temperature of the alkali-soluble resin is greater than 100° C.;

[0011] The alkali-soluble resin includes any one of styrene-maleic anhydride resin, polyester-modified acrylic resin, ethylene-acrylic acid resin, maleic anhydride polyolefin resin, and styrene-acrylic acid resin, or a combination of at least two thereof.

[0012] In the present invention, by introducing at least one carboxyl group and anhydride functional group into an alkali-soluble resin, the heat-resistant polymer particles can reduce the direct contact between nano-ceramic particles by covering and encapsulating, effectively reduce the surface energy of the nano-ceramic particles, thereby preventing the agglomeration of the particles, and the carboxyl group and the anhydride functional groups modify the surface of the nano-ceramic particles to change the surface properties from hydrophilic to lipophilic, so that the nano-ceramic particles are evenly distributed in the polymer matrix, and the introduced polymer particles can form a space barrier on the surface of the nano-ceramic particles to prevent the approach and aggregation of the nano-ceramic particles, thereby further enhancing the dispersion stability.

[0013] According to the present invention, as known to those skilled in the art, the alkali-soluble resin structural unit in the heat-resistant polymer particles means: a structural unit derived from an alkali-soluble resin in the heat-resistant polymer particles obtained by polymerization of raw materials including an alkali-soluble resin. Similarly, in the present invention, the main monomer structural unit, the functional monomer structural unit and the cross-linking monomer structural unit respectively mean structural units derived from the main monomer, the functional monomer and the cross-linking monomer in the heat-resistant polymer particles.

[0014] In the present invention, the glass transition temperature of the heat-resistant polymer particles may be 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc.

[0015] In the present invention, the glass transition temperature of the alkali-soluble resin may be 110° C., 120° C., 130° C., 140° C., 150° C. or 160° C., etc.

[0016] Preferably, the glass transition temperature of the main monomer is ≥100°C.

[0017] In the present invention, the glass transition temperature of the main monomer may be 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C. or higher.

[0018] In the present invention, the glass transition temperature of the functional monomer is ≥100°C, and can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or higher.

[0019] In the present invention, the functionality of the cross-linking monomer is ≥2.

[0020] The functionality of the crosslinking monomer can be 2, 3, 4 or 5, etc.

[0021] Preferably, the main monomer includes any one of styrene monomer, methylstyrene monomer, methacrylonitrile monomer, methyl methacrylate monomer, glycerol formal methacrylate, isobornyl acrylate monomer, and isobornyl methacrylate monomer, or a combination of at least two of them.

[0022] Preferably, the functional monomers include any one of sodium p-styrene sulfonate monomers, acrylamide monomers, methacrylamide monomers, acrylic acid monomers, methacrylic acid monomers, and itaconic acid monomers, or a combination of at least two of them.

[0023] The selection of the above-mentioned main monomers and functional monomers further highlights the functions of the heat-resistant polymer particles. For example, styrene monomer can improve the thermal stability, mechanical strength and ionic conductivity of the diaphragm while maintaining good electronic insulation, thereby improving the safety and performance of the battery; for example, methacrylamide monomer helps to improve the safety performance of the diaphragm under high temperature conditions, reduce the risk of thermal runaway, and improve the wettability of the electrolyte material to the composite diaphragm, thereby improving the injection efficiency.

[0024] Preferably, the cross-linking monomer includes one or a combination of two or more of diol diacrylate monomers, bisphenol A diacrylate monomers, azocycloalkane diacrylate monomers, divinyl aromatic hydrocarbon monomers, diol dimethacrylate monomers, bisphenol A dimethacrylate monomers, trimethylolpropane triacrylate monomers, trimethylolpropane trimethacrylate monomers, and pentaerythritol tetraacrylate.

[0025] The selection of the above-mentioned cross-linking monomers further highlights the functionality of the heat-resistant polymer particles. For example, diol diacrylate monomers can undergo photocuring or heat-initiated polymerization reactions, and can cross-link with functional groups on the diaphragm substrate or themselves to form a three-dimensional network structure, significantly enhancing the mechanical strength, heat resistance and chemical stability of the diaphragm.

[0026] In the heat-resistant polymer particles, the weight ratio of alkali-soluble resin: main monomer: functional monomer: cross-linking monomer is 5-10: 60-85: 5-20: 2-10, preferably 6-8: 65-80: 8-20: 2-5.

[0027] Preferably, the average particle size (D50) of the heat-resistant polymer particles is 50 to 1000 nm.

[0028] In the present invention, the average particle size of the heat-resistant polymer particles may be 50 nm, 200 nm, 400 nm, 600 nm, 800 nm or 1000 nm.

[0029] Preferably, the composition further comprises auxiliary agents, which include wetting agents, defoaming agents and anti-settling agents.

[0030] In the present invention, the wetting agent is selected from Tuile DS-960, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, fatty amine polyoxyethylene ether, or a combination of two or more thereof.

[0031] As a preferred technical solution of the present invention, fatty amine polyoxyethylene ethers illustratively include but are not limited to: C18 fatty amine polyoxyethylene ether, tallow amine polyoxyethylene ether, fatty amine polyoxyethylene ether 1815, and PEG-2 hydrogenated tallow amine.

[0032] As a preferred technical solution of the present invention, alkylphenol polyoxyethylene ethers illustratively include but are not limited to: nonylphenol polyoxyethylene ether and octylphenol polyoxyethylene ether.

[0033] As a preferred technical solution of the present invention, fatty acid polyoxyethylene ethers illustratively include but are not limited to: oleic acid polyoxyethylene ether, stearic acid polyoxyethylene ether, lauric acid polyoxyethylene ether, and emulsifier SG-9.

[0034] As a preferred technical solution of the present invention, fatty alcohol polyoxyethylene ethers illustratively include but are not limited to: AEO-3, AEO-5, AEO-7, AEO-9, Brij 30, Brij 35, and Brij 58.

[0035] In the present invention, the adhesive may be any of various adhesives commonly used in the art for separators, and preferably an acrylic adhesive.

[0036] In the present invention, the defoamer is selected from one or a combination of two or more of a fluorine-containing defoamer, a silicone oil defoamer, a modified organic silicon defoamer, and a bio-based defoamer.

[0037] In the present invention, the anti-settling agent is selected from one or a combination of two or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and sodium polyacrylate.

[0038] Preferably, the average particle size of the nano-ceramic particles is 50 to 1000 nm.

[0039] In the present invention, the average particle size of the nano-ceramic particles can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm.

[0040] In a second aspect, the present invention provides a composite ceramic diaphragm, comprising a base membrane and a slurry coated on the base membrane, wherein the slurry is prepared from the diaphragm slurry composition of the first aspect.

[0041] In the present invention, the base film illustratively includes, but is not limited to, a polyolefin base film, a non-woven fabric separator, a porous polymer film, a porous polymer film, and a polyethylene terephthalate base film.

[0042] At the same time, the present invention also discloses that the diaphragm slurry composition comprises the following components in parts by weight:

[0043] 35-80 parts of nano ceramic particles;

[0044] 35-80 parts of heat-resistant polymer particles;

[0045] 8 to 16 parts of binder;

[0046] 230-300 parts of deionized water;

[0047] 0.5-7 parts of additives;

[0048] Wherein, the number of nano ceramic particles can be 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79 or 80 parts;

[0049] The number of parts of the heat-resistant polymer particles can be 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79 or 80 parts;

[0050] The number of parts of the binder can be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts;

[0051] The number of parts of the auxiliary agent can be 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1.0 part, 1.1 part, 1.2 part, 1.3 part, 1.4 part, 1.5 part, 1.6 part, 1.7 part, 1.8 part, 1.9 part, 2.0 part, 2.1 part, 2.2 part, 2.3 part, 2.4 part, 2.5 part, 2.6 part, 2.7 part, 2.8 part, 2.9 part, 3.0 part, 3.1 part, 3.2 part, 3.3 part, 3.4 part, 3.5 part, 3.6 part, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 or 7 parts.

[0052] Preferably, the diaphragm slurry composition comprises the following components in parts by weight:

[0053] 35-80 parts of nano ceramic particles;

[0054] 35-80 parts of heat-resistant polymer particles;

[0055] 8 to 16 parts of binder;

[0056] 230-300 parts of deionized water;

[0057] Wetting agent 0.5-3 parts;

[0058] Defoaming agent 0.5-1 part;

[0059] 0.5-3 parts of anti-settling agent;

[0060] Wherein, the number of parts of the wetting agent can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts;

[0061] The amount of the defoaming agent can be 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1.0 part;

[0062] The number of parts of the anti-settling agent can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0 parts.

[0063] In the present invention, the preparation method of the diaphragm slurry composition comprises the following steps:

[0064] S1. In a nitrogen system, an alkali-soluble resin, a main monomer, a cross-linking monomer, a functional monomer and deionized water are subjected to emulsion polymerization to obtain heat-resistant polymer particles;

[0065] S2. The heat-resistant polymer particles, nano-ceramic particles, binder and additives are first dispersed in a sander, and then stirred in a stirrer to obtain a diaphragm slurry composition.

[0066] Preferably, the substrate layer is selected from any one of a polyethylene porous film, a polypropylene porous film, a polypropylene film, a polyethylene film, a polypropylene three-layer composite porous film, and a polybutylene porous film.

[0067] In a third aspect, the present invention provides a secondary battery, wherein the secondary battery comprises the composite ceramic separator as described in the second aspect.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] (1) The diaphragm slurry composition of the present invention has the function of dispersing nano-ceramic particles, avoiding the phenomenon of agglomeration of nano-ceramic particles, and can form a stable and evenly distributed composite coating of heat-resistant polymer particles and nano-ceramic particles in the diaphragm, thereby improving the mechanical strength and heat shrinkage resistance of the diaphragm;

[0070] (2) The heat-resistant polymer particles of the present invention can be used as a dispersion medium and can be adsorbed on the surface of the nano-ceramic particles, changing their surface properties from hydrophilic to lipophilic, which helps to evenly distribute the nano-ceramic particles in the polymer matrix and improve the wettability of the electrolyte.

[0071] (3) The present invention introduces an alkali-soluble resin, a main monomer, a functional monomer and a cross-linking monomer. By controlling the Tg of the alkali-soluble resin and the heat-resistant polymer particles, the heat-resistant polymer particles present a heat-resistant particle morphology, and the introduced polymer material has a small density, which can reduce the quality of the diaphragm, thereby reducing the quality of the secondary battery.

[0072] (4) The composite ceramic diaphragm of the present invention has high thermal stability and high mechanical strength, as well as wettability to electrolyte and internal ion conductivity of secondary batteries, and is lighter and thinner than diaphragms made of inorganic materials. DETAILED DESCRIPTION

[0073] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0074] Example 1

[0075] This embodiment provides a diaphragm slurry composition, which is prepared by the following steps:

[0076] Add 230 parts of deionized water and 0.5 parts of anti-settling agent sodium carboxymethyl cellulose into a high-speed mixer and disperse at a low speed. After dispersing for 30 minutes, add 35 parts of nano-ceramic particles and 35 parts of heat-resistant polymer particles. After stirring and dispersing by sand milling for 0.5 hours, transfer to the mixer again, add 0.5 parts of wetting agent alkylphenol polyoxyethylene ether, 8 parts of acrylic acid ester binder SC801 and 0.5 parts of modified silicone defoamer, stir at a low speed for 30 minutes and then discharge to obtain a diaphragm slurry composition.

[0077] This embodiment provides a composite ceramic diaphragm, which is prepared by the following steps: coating the diaphragm slurry composition on a base film, and rolling it up to obtain a composite ceramic diaphragm;

[0078] This embodiment also provides a heat-resistant polymer particle, which is prepared by the following steps:

[0079] 15 parts of styrene-maleic anhydride resin (Tg is 155°C) and 85 parts of deionized water are added to a reactor, nitrogen is introduced for 30 minutes, the closed container is heated to 80°C, ammonia water is slowly added to adjust the pH to 7, and the temperature is raised to 80°C after stirring until the polyester modified acrylic resin is dissolved, 0.3 parts of ammonium persulfate and 10 parts of deionized water are added, and then 135 parts of styrene, 30 parts of methacrylamide, 3 parts of methacrylic acid, 5 parts of sodium p-styrene sulfonate, 5 parts of 1,6-hexanediol diacrylate, 1 part of emulsifier sodium dodecylbenzene sulfonate, and 150 parts of water are uniformly added dropwise to the reactor at 85°C. The total dropping time is 4 hours. After the dropping is completed, the temperature is kept for 4 hours. After cooling, heat-resistant polymer particles are obtained. The Tg is detected to be 155°C. The average particle size of the heat-resistant polymer particles is 250nm as detected by a nanoparticle size analyzer.

[0080] Example 2

[0081] This embodiment provides a diaphragm slurry composition, which is prepared by the following steps:

[0082] Add 250 parts of deionized water and 2 parts of anti-settling agent sodium carboxymethyl cellulose in a high-speed mixer and disperse at a low speed. After dispersing for 30 minutes, add 50 parts of nano-ceramic particles and 60 parts of heat-resistant polymer particles. After stirring and dispersing by sand mill for 1.5 minutes, transfer to the mixer again, add 1 part of wetting agent alkylphenol polyoxyethylene ether, 12 parts of acrylic acid ester binder SC801 and 1 part of modified silicone defoamer, stir at a low speed for 30 minutes and then discharge the material to obtain a diaphragm slurry composition.

[0083] This embodiment provides a composite ceramic diaphragm, which is prepared by the following steps: coating the diaphragm slurry composition on a base film, and rolling it up to obtain a composite ceramic diaphragm;

[0084] This embodiment also provides a heat-resistant polymer particle, which is prepared by the following steps:

[0085] 15 parts of styrene-maleic anhydride resin (Tg is 155°C) and 85 parts of deionized water are added to a reactor, nitrogen is introduced for 30 minutes, the closed container is heated to 80°C, ammonia water is slowly added to adjust the pH to 8, the polyester modified acrylic resin is stirred to be completely dissolved and then the temperature is raised to 80°C, 0.3 parts of ammonium persulfate and 10 parts of deionized water are added, and then 145 parts of styrene, 20 parts of methacrylamide, 3 parts of methacrylic acid, 5 parts of sodium p-styrene sulfonate, 5 parts of 1,6-hexanediol diacrylate, 1 part of emulsifier sodium dodecylbenzene sulfonate, and 150 parts of water are uniformly added dropwise to the reactor at 85°C, the total dropping time is 4 hours, and the temperature is kept for 4 hours after the dropping is completed. Heat-resistant polymer particles are obtained by cooling, and their Tg is detected to be 152°C. The average particle size of the heat-resistant polymer particles is 400nm as detected by a nanoparticle size analyzer.

[0086] Example 3

[0087] This embodiment provides a diaphragm slurry composition, which is prepared by the following steps:

[0088] Add 300 parts of deionized water and 3 parts of anti-settling agent sodium carboxymethyl cellulose in a high-speed mixer and disperse at a low speed. After dispersing for 30 minutes, add 45 parts of nano-ceramic particles and 80 parts of heat-resistant polymer particles. After stirring and dispersing by sand milling for 2 hours, transfer to the mixer again, add 3 parts of wetting agent alkylphenol polyoxyethylene ether, 16 parts of acrylic acid ester binder SC801 and 1 part of modified silicone defoamer, stir at a low speed for 30 minutes and then discharge the material to obtain a diaphragm slurry composition.

[0089] This embodiment provides a composite ceramic diaphragm, which is prepared by the following steps: coating the diaphragm slurry composition on a base film, and rolling it up to obtain a composite ceramic diaphragm;

[0090] This embodiment also provides a heat-resistant polymer particle, which is prepared by the following steps:

[0091] 15 parts of acrylic resin (Tg is 118°C) and 85 parts of deionized water are added to the reactor, nitrogen is introduced for 30 minutes, the sealed container is heated to 80°C, ammonia water is slowly added to adjust the pH to 9, stirred until the polyester modified acrylic resin is completely dissolved, and then heated to 80°C, 0.3 parts of ammonium persulfate and 10 parts of deionized water are added, and then 155 parts of methyl styrene, 10 parts of acrylamide, 3 parts of methacrylic acid, 5 parts of sodium p-styrene sulfonate, 5 parts of trimethylolpropane triacrylate, 1 part of emulsifier sodium dodecylbenzene sulfonate, and 150 parts of water are uniformly added to the reactor at 85°C, the total dropping time is 4h, and the temperature is kept for 4h after the dropping is completed, and the heat-resistant polymer particles are obtained by cooling. Its Tg is detected to be 170°C, and the average particle size of the heat-resistant polymer particles is 500nm as detected by a nanoparticle size analyzer.

[0092] Comparative Example 1

[0093] Compared with Example 2, no polyester-modified acrylic resin is added.

[0094] Comparative Example 2

[0095] Compared with Example 2, no functional monomer is added.

[0096] Comparative Example 3

[0097] Compared with Example 2, no crosslinking monomer is added.

[0098] Comparative Example 4

[0099] Compared with Example 2, phenolic resin is used to replace polyester modified acrylic resin.

[0100] Comparative Example 5

[0101] Compared with Example 2, no heat-resistant polymer particles are added, and an equal amount of nano-ceramic particles are used instead.

[0102] Performance Testing

[0103] The test items of the present invention are: electrolyte wettability, air permeability time, and heat shrinkage resistance.

[0104] The test method of electrolyte wettability is as follows: the diaphragm prepared by the scheme of the present invention is cut into a specification of 5×100 mm, 0.1 μL of lithium salt electrolyte is dropped, and the droplet diffusion length is tested;

[0105] The test method of air permeability time is: using Gurley air permeability instrument for testing;

[0106] The test method for heat shrinkage resistance is: cut the diaphragm prepared by the scheme of the present invention into a specification of 100×100 mm, place it between two A4 papers, place it on an iron plate, transfer it to a 130°C oven and bake it for 1 hour, and test the change rate of the longitudinal width (MD) and the transverse width (TD) before and after.

[0107] The composite ceramic diaphragms prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for their air permeability time, thickness and surface density, and heat shrinkage resistance at 130° C. The test results are shown in Table 1.

[0108] Table 1

[0109]

[0110] The experimental results show that:

[0111] The present invention uses alkali-soluble resin, main monomer, functional monomer and cross-linking monomer as main components to form heat-resistant polymer particles, which replace part of nano-ceramic particles for ceramic diaphragms. Under the same thickness, compared with diaphragms made of inorganic materials, it has lower surface density, shorter air permeability, high electrolyte wettability, high thermal stability and thinner weight.

[0112] Comparing Examples 1-3 with Comparative Example 1, the introduction of alkali-soluble resin can enhance the dispersion of nano-ceramic particles, avoid the agglomeration of nano-ceramic particles, help the nano-ceramic particles to be evenly distributed in the polymer matrix, and enhance the wettability of the electrolyte.

[0113] Comparing Example 2 with Comparative Example 2, the introduction of high Tg functional monomers can also effectively improve the electrolyte wettability of the ceramic diaphragm, and is also beneficial to improving the bonding force between the nano-ceramic particles and the diaphragm, further improving the heat shrinkage resistance of the diaphragm;

[0114] Comparing Example 2 with Comparative Examples 3 and 5, the introduction of the cross-linking monomer has a significant effect on the heat shrinkage resistance of the composite ceramic diaphragm, and the cross-linking monomer can further improve the thermal stability of the heat-resistant polymer particles.

[0115] Comparing Example 2 with Comparative Example 4, using a water-soluble resin without carboxyl or anhydride groups, such as a phenolic resin, the emulsion polymerization reaction system has poor stability and is prone to agglomeration.

[0116] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A diaphragm slurry composition, characterized in that: The invention comprises heat-resistant polymer particles, nano-ceramic particles and a binder, wherein the heat-resistant polymer particles comprise an alkali-soluble resin structural unit, a main monomer structural unit, a functional monomer structural unit and a cross-linking monomer structural unit, and the glass transition temperature of the heat-resistant polymer particles is ≥150°C; The alkali-soluble resin includes at least one of a carboxyl group and an acid anhydride, and the glass transition temperature of the alkali-soluble resin is greater than 100° C.; The alkali-soluble resin includes any one of styrene-maleic anhydride resin, polyester-modified acrylic resin, ethylene-acrylic acid resin, maleic anhydride polyolefin resin, and styrene-acrylic acid resin, or a combination of at least two thereof.

2. The diaphragm slurry composition according to claim 1, characterized in that In the heat-resistant polymer particles, the weight ratio of alkali-soluble resin: main monomer: functional monomer: cross-linking monomer is 5-10: 60-85: 5-20: 2-10.

3. The diaphragm slurry composition according to claim 1, characterized in that The main monomer includes any one of styrene monomer, methylstyrene monomer, methacrylonitrile monomer, methyl methacrylate monomer, glycerol formal methacrylate, isobornyl acrylate monomer, and isobornyl methacrylate monomer, or a combination of at least two of them.

4. The diaphragm slurry composition according to claim 1, characterized in that The functional monomers include any one of sodium p-styrene sulfonate monomers, acrylamide monomers, methacrylamide monomers, acrylic acid monomers, methacrylic acid monomers, and itaconic acid monomers, or a combination of at least two of them.

5. The diaphragm slurry composition according to claim 1, characterized in that: The cross-linking monomer includes one or a combination of two or more of diol diacrylate monomers, bisphenol A diacrylate monomers, azacycloalkane diacrylate monomers, divinyl aromatic hydrocarbon monomers, diol dimethacrylate monomers, bisphenol A dimethacrylate monomers, trimethylolpropane triacrylate monomers, trimethylolpropane trimethacrylate monomers, and pentaerythritol tetraacrylate.

6. The slurry composition according to claim 1, characterized in that The average particle size of the heat-resistant polymer particles is 50 to 1000 nm.

7. The diaphragm slurry composition according to claim 1, characterized in that: The invention also comprises an auxiliary agent, wherein the auxiliary agent comprises at least one of a wetting agent, a defoaming agent and an anti-settling agent.

8. A composite ceramic diaphragm, characterized in that: The composite ceramic diaphragm comprises a base membrane and a slurry coated on the base membrane, and the slurry is prepared from the diaphragm slurry composition according to any one of claims 1 to 7.

9. A secondary battery, characterized in that: The secondary battery comprises the composite ceramic separator as claimed in claim 8.

Citation Information

Patent Citations

  • High-temperature-resistant binder for lithium battery ceramic diaphragm and preparation method of high-temperature-resistant binder

    CN113583532A

  • High-temperature-resistant ceramic diaphragm as well as preparation method and application thereof

    CN118213708A